Analisis Teori dan Referensi Pembelajaran Bilingual: Metode, Teknik, Strategi, Evaluasi, dan Aspek Pembelajaran Komprehensif - Irafany, Marcella Nadya; Divanggi, Ainida; Hanifatunnisa, Maulfi; Zahro, Ilma Az; Widyasepti, Rebecca Amellya; Iswara, Putri Dewani; Widagdo, Arif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the theory, methods, techniques, strategies, and evaluation in the implementation of bilingual learning at the elementary school level. The study was conducted through a literature study approach, where data was obtained from various sources of scientific literature and analyzed descriptively. The findings show that bilingual learning contributes significantly to improving language competence, developing cognitive abilities, and improving students’ academic achievement. Learning models that have proven effective include an integrated thematic approach, implementing structured language rotation, utilizing interactive digital media, and integrating cultural values from both languages used. The evaluation process is carried out through formative and summative assessments, including portfolios, classroom observations, and competency-based tests. However, the implementation of bilingual learning still faces several obstacles such as limited educators who are fluent in two languages, minimal availability of appropriate teaching materials, and variations in language abilities between students. Therefore, an integrated strategy is needed, including ongoing teacher training, developing an adaptive bilingual curriculum, and collaboration from various parties to ensure the success of the implementation of bilingual learning optimally and sustainably.